Pengaruh Media Sosial TikTok dan Regulasi Emosi Terhadap Perubahan Suasana Hat - Adinda, Maurael; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study aims to determine the influence of Tiktok social media users and emotion regulation on mood in grade XI students of Hutama Bekasi High School. This study uses a quantitative method. The population in this study is 242 with a sample of 149 respondents with a simple random sampling technique. The data collection method uses a Likert scale model. The data processing in this study was analyzed using the Simple Linear Regression method and and Multiple Linear Regression via JASP 0.18.3.0 for windows program. The results of the study showed that 1) there was an influence of TikTok social media on mood changes (r = 0.325 and p = 0.001 < 0.05); 2) there is an effect of emotional regulation on mood changes (r = 0.582 and p = 0.001 < 0.05); 3) there was an influence of TikTok social media and Emotion Regulation on mood changes (r = 0.682 and p = 0.001 < 0.05). This shows that there is an influence on TikTok social media and emotional regulation of mood changes for grade XI students of Hutama Bekasi High School.